Facial muscles and its modiolus: a review of embryology, comparative anatomy, morphology and applied anatomy - Abas, Razif; Choy, Ker Woon; Alias, Aspalilah; Kamaruzzaman, Mohd Amir; Mohd Noor, Nor Farid; Harun, Ahmad Mukifza; Mohd Nor, Nurul Huda (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2021)
The modiolus of the face manifests the interesting landmark for facial muscles attachment. The strong connective tissue fibres play an important role in the clinical setting, especially in the aesthetic and dental surgeries. In the fourth week of intrauterine life, the development of the modiolus evolves in accordance with the growth of muscles of facial expression. Microscopically, a white, tendinous structure with the thick irregular collagenous connective tissue of collagen fibres predominance appeared to be the modiolus. Modiolus is morphologically a fibromuscular muscle situated on the lateral border of the mouth. The formation of the nasolabial fold is important and a well-developed modiolus provide a toned face. Several works of literature forementioned the number of facial muscles attached to the modiolus but no definitive similarity are identified. This review summarizes the updated morphological features and applied anatomy of the facial modiolus with its muscle attachment.